Could more thoughtful practice of complexity, design thinking and values-based organising address some of the limitations of current management and organising paradigms?. (2016) - Sewchurran, Kosheek; Philipp, Felix; Baets, Walter; McDonogh, Jennifer
The concepts central to this special issue: complexity, design thinking and values-based organising are not typically discussed together despite all three concepts being concerned with new, innovative ways of organising. When these concepts are used together the intent is to propose a revitalisation of the means and ends of organising. This paper explores the conceptual integration of these concepts by focusing instead on the systems of organising they encourage. The goal of this exploration is to deepen interest in the underlying systems that inform the ideas of complexity, design thinking and values-based organising. We believe there is a philosophy of organising implicit in each of these three concepts that is, as yet, not coherently articulated. More elaboration, such as that is being done in this special issue, is necessary to avoid the concepts being applied superficially. It is argued in this paper that more thoughtful practice of complexity, design thinking and values-based organising can address some of the limitations of current management and organising paradigms, but to sustain the effort a complex systems grounding is needed.